MENINJAU KEDUDUKAN PELAKU RIDDAH DAN HUKUMAN MATI BAGI PELAKU RIDDAH BERDASARKAN HUKUM ISLAM DAN HAK ASASI MANUSIA DALAM SUDUT PANDANG ISLAM - Bimasakti, Muhammad Adiguna; Raouf, Nadim (Journal of Islamic Law Studies, 2021)
Riddah is an act of apostasy in Islamic faith. Some texts of the hadits (sayings of The Prophet PBUH) indicate that the apostate shall be punished with death sentence. Beside, the apostate will also lose some of his/her rights according to Islamic Sharia. But there is also a principle of Freedom of Religion in quranic text as we read in Surah Albaqarah (chapter 2) verse 256 which says: “There is no compulsion in religion”. This also indicates that the Freedom of Religion in Islamic perspective is guaranteed, and cannot be taken. Thus this writing tries to elaborate the two which are the Freedom of Religion principle and Capital Punishment / Jarimah for apostasy from the perspective of Human Right especially from the “Cairo Declaration on Human Rights in Islam” which was declared in Cairo, Egypt in 1990.